2022
DOI: 10.22605/rrh7219
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adolescent birth in Indonesia: a national survey

Abstract: Introduction: Adolescent birth has many negative impacts on the development of a country. Preparing for pregnancy needs to be done from adolescence so that adolescents and women are healthy during pregnancy and give birth to healthy babies. In Indonesia, the adolescent birth rate is still high. This study aimed to identify the determinants of adolescent birth (birth at ages Rural and Remote Health rrh.org.au

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…However, the results of studies in Europe stated that fertility was lower due to the high rate of delay in pregnancy in urban areas 21 and also the results of studies in Nigeria which showed differences with the findings in this study, namely that living in rural areas and the age at first marriage contributed to the high number of children. 22,23 The assumption that those with a high level of education will have a few children was not proven in this study after being controlled by other factors. 11 Higher education has a positive correlation with the desire to have two or more children because it is related to "individual agency" in determining their fertility preferences, including religious norms, child values, and ideal preferences for the number of children which are also significant in this study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the results of studies in Europe stated that fertility was lower due to the high rate of delay in pregnancy in urban areas 21 and also the results of studies in Nigeria which showed differences with the findings in this study, namely that living in rural areas and the age at first marriage contributed to the high number of children. 22,23 The assumption that those with a high level of education will have a few children was not proven in this study after being controlled by other factors. 11 Higher education has a positive correlation with the desire to have two or more children because it is related to "individual agency" in determining their fertility preferences, including religious norms, child values, and ideal preferences for the number of children which are also significant in this study.…”
Section: Discussionmentioning
confidence: 90%
“…This condition decreased to an average birth rate of 3.76 and then rose again to 3.84 in 2018-2019 respectively. The lowest birth rate for women with AFM [20][21][22][23][24] still occurs in Java and Bali, namely 2.55 which then decreased to 2.01 in 2018. However, this condition increased again in 2019 with an average birth rate of to 2.44.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…21 A previous study showed that most adolescent births were from mothers with a low education level. 22 Women with too many children and unqualified ANC will have a 1.47 times higher chance of giving birth to LBW babies than women with too many children and qualified ANC. This was in accordance with research conducted in Padang, mothers with less than four ANC visits were more likely to give birth to LBW babies compared to mothers with four ANC visits.…”
Section: Discussionmentioning
confidence: 99%
“…Even even though the unemployment rate of VHS graduates in Indonesia is still generally tall. Concurring to [8] information from the Central Measurements Organization, in Admirable 2020, the number of specialists was 138.22 million, an increment of 2.36 million compared to Eminent 2019. The open unemployment rate in Eminent 2020 was 7.07%, at that point expanded by 1.84% focuses compared to Eminent 2019.…”
Section: Introductionmentioning
confidence: 99%